2017
DOI: 10.7554/elife.25605
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal analyses in zebrafish and medaka reveal that harnessing the immune response promotes cardiac regeneration

Abstract: Zebrafish display a distinct ability to regenerate their heart following injury. However, this ability is not shared by another teleost, the medaka. In order to identify cellular and molecular bases for this difference, we performed comparative transcriptomic analyses following cardiac cryoinjury. This comparison points to major differences in immune cell dynamics between these models. Upon closer examination, we observed delayed and reduced macrophage recruitment in medaka, along with delayed neutrophil clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
354
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(387 citation statements)
references
References 55 publications
10
354
1
1
Order By: Relevance
“…In bilaterians, unbiased transcriptomics/proteomics approaches have proven useful to determine the genetic programs involved in the regeneration of complex structures, such as body parts in planarians (Kao et al, 2013) or Hydra (Petersen et al, 2015), appendages in zebrafish, lizards, salamanders (Hutchins et al, 2014;Bryant et al, 2017;Rabinowitz et al, 2017), heart in zebrafish (Lai et al, 2017) and mammals (Quaife-Ryan et al, 2017), lens in salamanders (Looso et al, 2013). These programs drive wound healing, stem cell recruitment and/or somatic tissue re-specification and 3D-patterning, the latter including the re-activation of specific developmental patterning mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In bilaterians, unbiased transcriptomics/proteomics approaches have proven useful to determine the genetic programs involved in the regeneration of complex structures, such as body parts in planarians (Kao et al, 2013) or Hydra (Petersen et al, 2015), appendages in zebrafish, lizards, salamanders (Hutchins et al, 2014;Bryant et al, 2017;Rabinowitz et al, 2017), heart in zebrafish (Lai et al, 2017) and mammals (Quaife-Ryan et al, 2017), lens in salamanders (Looso et al, 2013). These programs drive wound healing, stem cell recruitment and/or somatic tissue re-specification and 3D-patterning, the latter including the re-activation of specific developmental patterning mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Heart regeneration potential varies considerably between species as well as with age. While zebrafish, neonatal mouse and neonatal human hearts can replace dead or lost cardiomyocytes rapidly with new heart muscle (1)(2)(3)(4)(5), medaka (6,7), cave fish (8), as well as adult mice and human hearts (9) show only poor repair. Numerous studies are, therefore, looking into the underlying principles and mechanisms that promote, or prevent, effective cardiac regeneration to establish a basis for therapeutic intervention (10).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages are known regulators of cardiac regeneration in zebrafish and fibrosis in non-regenerating species (Aurora et al, 2014; Frantz and Nahrendorf, 2014; Lai et al, 2017). Colony stimulating factor receptor 1+ (Csfr1+) macrophages were stained in both injured and remote regions of the heart following injury to determine their behavior in the grass carp (Chen et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Proliferation of cardiomyocytes is a known driver of cardiac regeneration in non-mammalian species and neonatal mammals (Cano-Martínez et al, 2010; Flink, 2002; Gonzalez-Rosa et al, 2011; Lai et al, 2017; Liao et al, 2017; Porrello et al, 2011; Sallin et al, 2015; Schnabel et al, 2011; Stockdale et al, 2018; Vargas-González et al, 2005; Yu et al, 2018); further, a regenerative phenotype has not yet been reported in the absence of cardiomyocyte proliferation (Ito et al, 2014; Lin and Pu, 2014; Marshall et al, 2017). However, the recent finding of widespread cardiomyocyte proliferation in non-regenerative Pachón Astyanax mexicanus suggests that this behavior is not the sole factor that dictates a regenerative response (Stockdale et al, 2018).…”
Section: Discussionmentioning
confidence: 99%